PENGARUH TERAPI AL-QUR’AN SURAH AL-ISRA’:70 UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK DI SMP KARTIKA 1-5 PEKANBARU - Rizka Amiriza; Tri Umari; Syarilfiddin Syarilfiddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the self-confidence of students before and after the Qur'anic surah Al-Isra':70 therapy was given through group guidance and to know the influence of Al-Qur’an surah Al-Isra':70 therapy to increase self-confidence through group guidance. This research was conducted in SMP Kartika 1-5 Pekanbaru on 8 subjects with purposive sampling technique. The research design was pre-experiment with one group pre-test post-test model. The instrument of data collection used is the scale of self-confidence measurement. The results showed that there were differences in students 'self-confidence before and after being given therapy Al-Qur’an surah Al-Isra':70 with a significance value of 0.011 <0.05. In addition, based on the Spearman rank test it is known that there is a significant influence between the therapy of 'Al-Qur'an surah Al-Isra’:70 to increase students' self-confidence with a significance value of 0.001 <0.05. The therapeutic effect of Al-Qur’an surah Al-Isra':70 to increase students' self-confidence is 84.82% while 15.18% is influenced by other factors that come from within and from the student's environment. From the results obtained, it is recommended that educational institutions should be able to continue implementing IMTAQ such as relaxation, reading the Qur'an correctly by living it, deepening the Qur'an and learning religion to encourage the development of thoughts, perceptions, insights, calmness and attitudes more positive students.Key Words: Al-Qur’an Surah Al-Isra’:70 Therapy, Self-Confidence, Group Guidance